Acetate alters the process of lipid metabolism in rabbits. (4th December 2017) - Fu, C.; Liu, L.; Li, F.
Abstract : An experiment was conducted to investigate the effect of acetate treatment on lipid metabolism in rabbits. New Zealand Rabbits (30 days, n =80) randomly received a subcutaneous injection (2 ml/injection) of 0, 0.5, 1.0 or 2.0 g/kg per day body mass acetate (dissolved in saline) for 4 days. Our results showed that acetate induced a dose-dependent decrease in shoulder adipose ( P <0.05). Although acetate injection did not alter the plasma leptin and glucose concentration ( P >0.05), acetate treatment significantly decreased the plasma adiponectin, insulin and triglyceride concentrations ( P <0.05). In adipose, acetate injection significantly up-regulated the gene expression of peroxisome proliferator-activated receptor gamma (PPARγ), CCAAT/enhancer-binding protein α ( C/EBPα ), differentiation-dependent factor 1 ( ADD1 ), adipocyte protein 2 ( aP2 ), carnitine palmitoyltransferase 1 ( CPT1 ), CPT2, hormone-sensitive lipase ( HSL ), G protein-coupled receptor ( GPR41 ), GPR43, adenosine monophosphate-activated protein kinase α 1 ( AMPKα1 ), adiponectin receptor ( AdipoR1 ), AdipoR2 and leptin receptor. In addition, acetate treatment significantly increased the protein levels of phosphorylated AMPK α, extracellular signaling-regulated kinases 1 and 2 (ERK1/2), p38 mitogen-activated protein kinase (P38 MAPK) and c-jun amino-terminal kinase (JNK). In conclusion, acetate up-regulated the adipocyte-specific transcription factors (PPAR γ, C/EBP α, aP2 and ADD1), which were associated with the activated GPR41/43 and MAPKs signaling. Meanwhile, acetate decreased fat content via the upregulation of the steatolysis-related factors (HSL, CPT1 and CPT2), and AMPK signaling may be involved in the process.